Profitability analysis and gender division of labour in duck rearing: a case of Kishoreganj district in Bangladesh (Progressive Agriculture, 2017)
Like all other poultry species, rearing duck in Bangladesh has every potential to give maximum return with minimum investments. Keeping the view in mind, this study was endeavored to concentrate valuable information on profitability performance as well as gender division of labor in duck farming. The study was conducted in purposively selected five villages of Karimganj upazila under Kishoreganj district. A structured interview schedule was pre-tested, improvised and finally used to collect data from the selected 50 duck raising farms. The study found that total cost for 1000 ducks were estimated at Tk. 74455.57 per batch. Average gross return, average gross margin and average net returns for 1000 ducks was estimated at Tk. 151780, Tk. 83296.5 and Tk. 77324.47 per batch, respectively. Benefit cost ratio was estimated to be 2.03 for duck rearing. There existed gender division of labor in duck rearing, as, in duck rearing, women paid more attention in caring tasks such taking ducks out of the shade, feeding, cleaning shelter, breaking of snails, etc. The average female contribution was 51% of total duck rearing activities, but their participation in household decision making process was not satisfactory. In rearing duck, farmers had faced a few challenges like incidence of disease, lack of access to credit, low training facilities, high feed costs, lack of veterinary services and medicine, lower selling price and less market facilities. To overcome these difficulties of duck rearing and make the business more profitable, the recommendations actions can be undertaken by the respective authorities as early as possible.Progressive Agriculture 27 (4): 482-489, 2016